Evaluación de la sustitución parcial de materias primas del producto “desinfect & clean” para la empresa C.I. Liansa S.A.S. (2019)
The company C.I. LIANSA S.A.S. (Bio2Eco), commercializes a line of industrial disinfectant products, which are intended to be affordable, ecological and of quality. The company is in the commercialization of a product called "Desinfect & Clean"; this product is sold to a shopping center in the city of Medellin, but it is not yet freely available in the market. One of the challenges of this project is to ensure that by making changes to the product, quality is maintained. A physical or chemical improvement is sought to obtain a final product that competes with the products that are already on the market, complying with the characteristics of a disinfectant that acts on gram positive and gram negative bacteria.